Biological Applications Of The Definite Integral - Goyibnazarov, Khabibulla; Umarov, Xabibulla (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Mathematical models have long been very successfully used in mechanics, physics, and astronomy. In the modern period, the role of mathematical methods in natural science is increasing. They are now widely used in both biology and chemistry. Mathematical models are also successfully applied here. This article contains some of these applications.